Overview of the change in the organization of the education system in Gabon - Ependja, Antoine Towaka; Mba, Jean Paulin Eyeghe (Open Science Journal, 2021)
The question of change in the organization is at the heart of the concerns of public policy managers. This article proposes to analyze the management of organizations in the educational system in Gabon. We have examined what is said and what is best done in the field in an attempt to identify this consideration by the theorists of change. As pointed out by several authors, particularly those who have investigated this issue, change is a stakeholder in the management of organizations. At the end of this literature review, we found that Gabon is not the only country to be confronted with the problem of change management in its education system. In conducting an education reform, it must take into account the balance of power within the organization. In order for the organization to achieve its goal, communication must become a permanent feature of human resources management. Thus, changing the education system is a titanic but achievable undertaking. The competence of the managers, the piloting mode and the management of human resources are determining factors in the process of change.